Influence Policy Corporate Social Responsibility to Intention Buy Starbucks Coffee Brand Image In Kediri - KUSWORO, AHMAD DZULFIKRI (International Journal of Business, Law, and Education, 2025)
This study aims to examine the influence of Corporate Social Responsibility (CSR) policies on purchase intention and brand image of Starbucks Coffee in Kediri. As a globally recognized brand, Starbucks has demonstrated a consistent commitment to CSR, which plays a key role in shaping consumer perceptions. Using a quantitative research method, data were collected through questionnaires distributed to Starbucks consumers in Kediri. The findings reveal that CSR policies implemented by Starbucks have a significant positive effect on its brand image. Additionally, these policies also positively influence consumers' purchase intentions. This indicates that consumers are more likely to purchase Starbucks products when they perceive the company to have a strong and genuine CSR commitment. The positive brand image fostered by CSR initiatives directly contributes to increased consumer interest and loyalty toward the brand. These results underscore the strategic value of CSR in enhancing brand reputation and driving consumer behavior. For Starbucks management, maintaining and developing CSR programs can be a powerful tool in sustaining market presence and customer engagement. Furthermore, the research offers insights for other companies aiming to build strong brand equity through responsible business practices. Emphasizing CSR not only contributes to social and environmental well-being but also provides a competitive advantage in influencing consumer purchase decisions.